TERMINAÇÃO DE BOVINOS EM PASTEJO - Carlos dos Santos Costa, Luan; Renan Dutra Santos , Aylpy; Gonçalves Silva, Arianny; Adely Collete Almada Silva , Brenda; de Aguillar Soares, Maxswel; Mendes Oliveira , Dalton (ANAIS DO ENIC, 2026)
-